Peran Teknologi Informasi dalam Keunggulan Kompetitif - Saputra, Nathania Adeline (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The Covid-19 pandemic has accelerated digital transformation in all sectors. The rise of revolution and change in all industries and economies today has an impact that cannot be avoided by all parties. Rapid developments in the world of digitalization and technology can be an opportunity for companies to take advantage of the use of technology. The industrial revolution 4.0 with VUCA conditions (Volatility, Uncertainty, Complexity, Ambiguity), encourages and requires digital transformation. The research results show that the role of information systems can create competitive advantages for companies. This research uses secondary data collection methods using analytical media and literature reviews from existing journals. It is hoped that this research can provide new knowledge for business owners and readers.